Nelly Don’s 1916 pink gingham apron frock: an illustration of the middle-class American housewife’s shifting role from producer to consumer - Whang, Mikyoung (Kansas State University, 2011)
Nell Donnelly created a stylish, practical, affordable pink gingham apron frock in 1916, selling out her first order of 216 dresses the first morning at $1 apiece at Peck’s Dry Goods Company in Kansas City. This study investigates the forces behind the success of her dress, and finds that during the early 20th century, woman’s role became modernized, shifting from that of producer to consumer, and that clothing—in particular, the housedress—was a visible reflection of this shift. Specific attributes contributed to the success of the apron frock in design and social perspective. First, her housedress incorporated current design elements including kimono sleeves, empire waistline, waist yoke, asymmetrical front closure, and ruffle trimmings sensibly. Socially, mass advertising and mass media articles promoted fashion consciousness in women to look as pretty as those in the ad or article. As a result, integrating trendy design elements into an affordable housedress along with the growing demand for a stylish, yet practical housedress guaranteed the success of Nelly Don’s pink gingham apron frock. As such, the availability and value of the apron frock provide a vivid illustration of woman’s shifting role: its popularity as an alternative to old-fashioned Mother Hubbard housedresses demonstrates both women’s new consumer awareness as well as their growing involvement in the public sphere.
Keywords: Nelly Don's 1916 pink gingham apron frock; House dress; Women's shifting roles; Modernization; Consumption culture; American History (0337); Home Economics (0386)